Bullying Analysis of Children with Special Needs in Elementary School: Analisis Bullying Terhadap Anak Berkebutuhan Khusus di Sekolah Dasar - Pranintasari, Riries; Wachidah, Kemil (Universitas Muhammadiyah Sidoarjo, 2021)
Bullying is an act that is currently happening and being discussed. Several cases of bullying occur in society, both in the social and educational world, which makes various parties more concerned, including the child protection commission, causing several negative impacts for the victims and also the perpetrators of bullying themselves. Various ways have been done to minimize the incidence of bullying in schools, including one of the National Commission for Child Protection urging the school to better protect and pay attention to their students. Theoretically, this research is useful to increase knowledge and broaden the horizons of researchers in the field of analyzing cases of bullying against Children with Special Needs (ABK). Practically, this research can provide recommendations or descriptions and views for readers, especially for parents and teachers in fostering good communication relationships with children and students who have special needs so that they can help to develop themselves optimally. This research is a qualitative approach with a case study method based on the philosophy of postpositivism, which is used to examine the condition of a natural object, where the researcher is the key instrument, the sampling of data sources is carried out purposively and snowballing, the collection technique is triangulation (combined). . The results of the research conducted among the types of bullying that often occur in Children with Special Needs at SD Muhammadiyah 2 Tulangan include being pushed, fooled, insulted, threatened, humiliated, and ostracized. In overcoming these problems the teacher provides reinforcement for Children with Special Needs (ABK) to be stronger mentally and physically to deal with bullying cases that occur in Children with Special Needs (ABK) and non-ABK. Special Needs (ABK) and non-ABK. For teachers to pay more attention and get closer to students who experience bullying in order to help solve problems that occur at school.